Cerebrospinal fluid tumor markers predict treatment response in a patient with carcinomatous meningitis. Issue 1 (January 2021) - Lin, Jiacai; Wu, Siting; Tian, Chenglin; Shi, Qiang
We report on a 56-year-old female patient diagnosed with carcinomatous meningitis caused by lung cancer. The diagnosis was confirmed by lung computed tomography, enhanced brain magnetic resonance imaging, histopathology, cerebrospinal fluid (CSF) cytology, and serum and CSF tumor markers. Genetic testing detected an epidermal growth factor receptor gene exon 19 deletion. The patient survived for 29 months after systemic treatment with gefitinib, radiotherapy, and chemotherapy. Dynamic monitoring of CSF and serum tumor markers was carried out during the treatment process. We considered that CSF tumor marker levels may have allowed the early diagnosis of meningeal carcinomatosis, and that systemic therapy in the early stage of the disease may prolong survival.